Phytochemical analysis of methanolic extract of Ulva rigida C.Ag. collected from Koothankuzhi Coast, Tirunelveli district, Tamil Nadu, India - Muthu Sheeba, M.; Peter Paul, J. John; Iniya Udhaya, C. (Journal of Drug Delivery and Therapeutics, 2018)
The present study was concentrated to explore the phytochemicals present in the methanolic extract of Ulva rigida C.Ag., collected from Koothankuzhi in the south east coast of Tamil Nadu, India.  The phytochemical analysis of methanolic extract was screened using the standard procedure for UV-Visible spectroscopic, HPLC and FTIR. The UV-Visible spectrum showed the compounds separated at the nm of 662, 603, 533 and 400 with the absorption 0.653, 0.331, 0.458 and 2.684 respectively. The qualitative HPLC fingerprint profile displayed fourteen compounds at different retention time of 1.770min, 2.230min, 2.540min, 2.870min, 3.090min, 3.377min, 3.900min, 4.257min, 4.797min, 5.340min, 5.853min, 6.520min, 7.730min and 9.220min. The result of FTIR analysis was found the presence of functional groups such as alkynes, sulfonic acids, carboxylic acids, carboxylic acid salt, aldehydes, aliphatic and unsaturated hydrocarbons.Keywords: Ulva rigida, UV-Visible, HPLC, FTIR